Synchronous borderline ovarian tumor with endometrioid endometrial carcinoma - from diagnosis to treatment. A Case study - Kolasa, Eliza; Paluch, Alicja; Kułak, Krzysztof (Journal of Education, Health and Sport, 2023)
Introduction The occurrence of two primary tumors at an interval of no more than two months is called a synchronous tumor. This also applies to female reproductive organs among which synchronous occurrence of ovarian and endometrial cancers is most frequently observed. This phenomenon is observed mainly in young women before menopause. A rare and problematic diagnostic situation is the synchronous co-occurrence of borderline ovarian carcinoma with endometrioid carcinoma of the endometrium. The diagnostic problem and treatment of this combination of cancers are presented in the following case. Case description: A 30-year-old female patient presented to the Gynecologic Oncology Department with a suspected malignant lesions of both ovaries. She underwent fertility-sparing surgery with preservation of the left ovary and uterus. Examination of the resected tissues revealed an endometrioid borderline tumor. During the next hospitalization, an excision of uterine polyps was performed, during which no neoplastic lesion of the endometrium was observed. Ultrasound examination, in which the endometrial lesion was also invisible, raised suspicion of cancer recurrence on the left ovary. The patient was scheduled for resection of the left ovary with the recurrence and hysterectomy. The histopathological examination performed confirmed the recurrence on the ovary and showed foci of G1 endometrioid carcinoma of the uterus. Conclusions Cases that meet the criteria for synchronous tumor occurrence should be considered. Appropriate diagnosis and selection of radical treatment could affect the curability of patients. Further research on rare combinations of synchronous neoplasms could be helpful in clinical practice.